2018
DOI: 10.1021/acs.analchem.7b05341
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Antibody-Functionalized Upconversion Nanoprobe

Abstract: Upconversion nanoparticles (UCNPs) are new optical probes for biological applications. For specific biomolecular recognition to be realized for diagnosis and imaging, the key lies in developing a stable and easy-to-use bioconjugation method for antibody modification. Current methods are not yet satisfactory regarding conjugation time, stability, and binding efficiency. Here, we report a facile and high-yield approach based on a bispecific antibody (BsAb) free of chemical reaction steps. One end of the BsAb is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…As is known, lanthanide ion (Ln 3+ )-doped upconversion nanoparticles (UCNPs) with notable merits such as large anti-Stokes shifts, negligible auto-fluorescence, excellent detection sensitivity, high penetration depth and good biocompatibility have the ability to emit UV, visible and NIR light under NIR laser irradiation, which make them promising candidates for visual tracking in the theranostic field. 33,34 Therefore, UCNPs can be selected as promising candidates for potential applications in biological labeling, 35,36 biological imaging, 37,38 sensing 7,39 and clinical therapeutics. 40,41 Up to now, considerable efforts have been devoted to the synthesis of nanocomposites based on UCNPs and CuS nanodots through specific chemical or physical combinations, which could provide extensive potential for the synergistic diagnosis and treatment of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, lanthanide ion (Ln 3+ )-doped upconversion nanoparticles (UCNPs) with notable merits such as large anti-Stokes shifts, negligible auto-fluorescence, excellent detection sensitivity, high penetration depth and good biocompatibility have the ability to emit UV, visible and NIR light under NIR laser irradiation, which make them promising candidates for visual tracking in the theranostic field. 33,34 Therefore, UCNPs can be selected as promising candidates for potential applications in biological labeling, 35,36 biological imaging, 37,38 sensing 7,39 and clinical therapeutics. 40,41 Up to now, considerable efforts have been devoted to the synthesis of nanocomposites based on UCNPs and CuS nanodots through specific chemical or physical combinations, which could provide extensive potential for the synergistic diagnosis and treatment of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that UCNPs coated with different ligands (silica shells, 40 charged polymers, 41 active small molecules, 42 biomacromolecules, 43 etc.) and/or covalently linked to functional groups (peptides, 44 folates, 45 antibodies, 46 etc.) can achieve cellular imaging via exocytosis and group-mediated action.…”
Section: Design Of Up-conversion Nanoprobes For Molecular Imagingmentioning
confidence: 99%
“…Lanthanide (Ln 3+ ) doped upconversion nanoparticles (UCNPs), featuring by unique luminescent properties including large Stokes shift, tunable emission spectrum and decay lifetime, zero autofluorescence background and high penetration depth into biological tissue, is emerging as a promising light carrier. The UCNPs are attractive in a wide array of applications [1][2][3][4][5][6][7] , such as graphics imaging and display [8][9][10] , anti-counterfeiting 11,12 , and biological labelling [13][14][15][16][17] . In order to expedite the practical applications of UCNPs, great research efforts have been paid to enhance the upconversion luminescence [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%